Pertanggungjawaban Pidana Bank dalam Pelanggaran Kegiatan Operasional Didasarkan pada Undang-Undang Nomor 10 Tahun 1998 - Johannes Ibrahim; Hassanain Haykal (Dialogia Iuridica, 2016)
Banks are the intermediation institutions which have important role in economic of a nation. In order to supervise and monitor bankong activities, government has issued Law Number 10 of 1998 on amandement of Law Number 7 of 1992 on banking which is blogated compulsive to all banking stakeholders. This law regulates administrative and criminal sanctions. In accordance with criminal sanction, any action determine as a violation based on its offence related to any norm. This article will examine operational vilogation, which qualified as crime offence. This article also examine bank accountability for every violation statedabove.